2019
DOI: 10.1159/000501730
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing Effect of <b><i>Lawsonia inermis</i></b>

Abstract: <b><i>Background:</i></b> <i>Lawsonia inermis</i>-extracted oil is known for therapeutic properties, especially wound healing. This study assesses the potential of this oil for wound healing in a rat model. <b><i>Methodology:</i></b> To assess the potential of <i>L. inermis-</i>extracted oil for wound healing, phytochemical, antibacterial, and antioxidant analyses were conducted. Uniform wound excision was induced on the dorsum of randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…Over the years, medicinal plants have been used to develop a variety of formulations that combat injuries such as wounds, burns and cuts [ 15 ]. Several ethno-medicinal plants have been used for medicinal applications thanks to their wide biological activities and medicinal applications due to counteracting oxidative stress potential, lesser costs and high safety margins [ 16 , 17 , 18 ]. Plant extracts are known to exhibit many pharmacological properties (anti-hyperlipidemic, anti-proliferative, and immunomodulatory, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, medicinal plants have been used to develop a variety of formulations that combat injuries such as wounds, burns and cuts [ 15 ]. Several ethno-medicinal plants have been used for medicinal applications thanks to their wide biological activities and medicinal applications due to counteracting oxidative stress potential, lesser costs and high safety margins [ 16 , 17 , 18 ]. Plant extracts are known to exhibit many pharmacological properties (anti-hyperlipidemic, anti-proliferative, and immunomodulatory, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…It was investigated in terms of its potential antioxidant components such as flavonoids and polyphenols [ 10 , 11 , 21 ]. Previous studies reported that it is a potential source of anticancer and antioxidant molecules [ 16 ]. It is a very rich source of valuable compounds, such as polyphenols, vitamins, flavonoids, carotenoids and carbohydrates [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several natural ingredients in dermocosmetic products have shown promising wound care choices [13,14]. One of the most interesting substances is snail mucus secretion, which is currently gaining popularity in the world of cosmetics and cosmeceuticals [15].…”
Section: Introductionmentioning
confidence: 99%
“…This comes in agreement with previous studies that described antibacterial properties of L. inermis and L. plantarum . 14 , 23 , 24 The MIC of L. plantarum could be decreased from 13mg/mL to 2 mg/mL when combined with L. inermis indicating a synergistic effect in case of L. plantarum with FIC (fraction inhibitory concentration) =0.5 . On the other side the combination had an antagonistic effect on L. inermis with MIC increased from 0.7 to 13 mg/mL with FIC (fraction inhibitory concentration) =9.…”
Section: Discussionmentioning
confidence: 95%